Dietary white button mushroom improved the growth, immunity, antioxidative status and resistance against heat stress in Nile tilapia (Oreochromis niloticus) - Mahmoud A.O. Dawood (2020)
© 2020 Elsevier B.V. This study was aimed at evaluating the growth, hematology, immune-related genes, antioxidative status and resistance against heat stress (HS) in Nile tilapia fed diets with white button mushroom (WBM) at 0, 0.5, 1, 2, and 4% for 60 days. The final body weight, weight gain, specific growth rate, and feed intake were significantly increased quadratically by increasing the level of WBM in the tilapia diet (P <.05). However, the feed conversion ratio was quadratically decreased (P =.003). No significant alterations were found in the hematological variables due to WBM supplementation except for the Hb, RBCs, and WBCs which showed the highest values in 2% level (P <.05). Before HS, the glucose and cortisol levels were significantly decreased by increasing the level of WBM with the highest value in fish fed the control (P <.05). After HS, lower glucose values were displayed in fish fed WBM at 1 or 2% than the control, while cortisol was decreased in fish fed 0.5, 1, and 2%. The lysozyme activity was significantly increased in 1, 2 or 4% levels either before or after HS (P <.05), while phagocytic activity (PA) and phagocytic index (PI) increased by WBM in all levels before HS. Before HS, SOD and CAT were significantly increased in 1 and 2% levels (P <.05), while MDA was lowered by WBM at all levels. After HS, SOD was increased and MDA was decreased by WBM at 0.5, 1 or 2% levels, while CAT and GPx were increased by 1 and 2% levels (P <.05). The relative expression of INF-γ, TNF-α, and IL-1β genes showed increased transcription by WBM at 2% either before or after HS (P <.05). However, HSP70 was decreased by supplementing WBM at 0.5 to 4% levels either before or after HS (P <.05). Based on the measured parameters, the requirement of dietary WBM for Nile tilapia is 2.15 to 2.75%. To conclude, WBM is recommended to cope with the impacts of heat stress on Nile tilapia aquaculture by improving the growth, antioxidative resistance, and immunity.